2010
DOI: 10.1177/1350507609357004
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of situated learning in organizations

Abstract: Situated learning theory posits that learning in organizations arises in the contexts and conditions of practical engagement, and time is an important dimension of activity and context of learning. However, time has primarily been conceptualized as an internal property of communities, buffered from social and organizational temporalities that shape rhythms of working and learning. This article examines how external temporalities affect situated learning through case studies of technical after-sales services. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 33 publications
0
43
0
1
Order By: Relevance
“…Time is implicitly incorporated in most research on OL, because learning involves improvement and progression over time (Lervik et al . ). Recently, an increasing number of studies have explicitly addressed aspects of the role of time in OL (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Time is implicitly incorporated in most research on OL, because learning involves improvement and progression over time (Lervik et al . ). Recently, an increasing number of studies have explicitly addressed aspects of the role of time in OL (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Such groups may have different understandings of knowledge (Cook and Brown, 1999) and negotiate meaning across boundaries. In this negotiation, they mobilize resources such as technological objects (Carlile, 2004;Levina and Vaast, 2005;Miettinen and Virkkunen, 2005;Nicolini et al, 2012), as well as direct relationships between individuals (Lervik et al, 2010). While some authors see the practices of different groups as remaining largely distinct, others propose a "trading zone", in which a new form of practice emerges (Chrisman, 1999;Kellogg et al, 2006) or articulate how the mediating objects are themselves changed through shared knowledge work (Ewenstein and Whyte, 2009;Mcgivern and Dopson, 2010).…”
Section: Theoretical Starting Points: Coordination Of Knowledge Workmentioning
confidence: 99%
“…Typically in experiential learning opportunities are created for individuals to learn from mistakes and grow personally as they gain new experiences (McLaughlin and Thorpe, 1993;Mumford, 1994). Researchers have concluded that such experience must be social and involve social learning, which engages others in the process (Lervik, Fahy and Easterby-Smith, 2010;McLaughlin and Thorpe, 1993). Experiential learning has been considered to provide a deeper more effective form of learning for students who experience it (Biggs, 1993;Entwistle and Ramsden, 1983) and it is often encouraged in many educational domains including entrepreneurship education (Gibb 2002).…”
Section: Entrepreneurial Learning and The Importance Of Experiential mentioning
confidence: 99%